Instructional design research trends towards digital transformation of education systems in ASEAN - Jajang Kusnendar; Deni Darmawan; Rusman Rusman (Himpunan Pengembang Kurikulum Indonesia, 2024)
The curriculum implementation in ASEAN countries is interesting to examine, especially in order to achieve the direction of the digital transformation roadmap of the education system. Research on instructional design can be used as one of the parameters to understand how the general description of implementation achieves curriculum goals. This study aims to examine instructional design research in ASEAN countries during the period 2018-2024 on the implementation of the national curriculum towards the digital transformation of the education system through (1) investigating the general description of instructional design research, (2) examining research characteristics from aspects of research objectives, (3) explaining the implications of findings both theoretically and practically. The documentation study was conducted through bibliometric analysis of articles with keywords against article titles containing the phrase